To multiply the polynomials \((3x - 1)(2x + 4)\), we can use the distributive property (often referred to as the FOIL method for binomials).
Let's distribute each term in the first polynomial to each term in the second polynomial:
-
Multiply \(3x\) by \(2x\): \[ 3x \cdot 2x = 6x^2 \]
-
Multiply \(3x\) by \(4\): \[ 3x \cdot 4 = 12x \]
-
Multiply \(-1\) by \(2x\): \[ -1 \cdot 2x = -2x \]
-
Multiply \(-1\) by \(4\): \[ -1 \cdot 4 = -4 \]
Now we combine all the results: \[ 6x^2 + 12x - 2x - 4 \]
Combine like terms (the \(12x\) and \(-2x\)): \[ 6x^2 + (12x - 2x) - 4 = 6x^2 + 10x - 4 \]
So, the product of the polynomials \((3x - 1)(2x + 4)\) is: \[ \boxed{6x^2 + 10x - 4} \]